Real-Time Assessment of Staphylococcus aureus Biofilm Disruption by Phage-Derived Proteins - Gutiérrez, Diana; Fernández, Lucía; Martínez, Beatriz; Ruas-Madiedo, Patricia; García, Pilar; Rodríguez, Ana (Frontiers in Microbiology, 2017)
A current focus of research is the development of new tools for removing bacterial biofilms in industrial settings. Bacteriophage-encoded proteins, such as endolysins, virion-associated peptidoglycan hydrolases (VAPGHs) and exopolysaccharide depolymerases, have been shown to be efficient against these structures. However, the current screening techniques for the identification of antibiofilm properties of phage-derived proteins have important shortcomings. The aim of this work was to use the rapid, reproducible and accurate technology “real-time cell analyzer’ (RTCA) for screening and comparing the antibiofilm ability of four phage-derived compounds, three lytic proteins (LysH5, CHAP-SH3b and HydH5-SH3b) and one exopolysaccharide depolymerase (Dpo7) against Staphylococcus aureus biofilms, which have been associated to recurrent contamination of food products. The data generated after biofilm treatment allowed the calculation of different antibiofilm parameters: 1) The minimum biofilm eradicating concentration that removes 50% of the biofilm (MBEC50) (ranging from 3.5±1.1 µM to 6.6±0.5 µM), 2) The lowest concentration needed to observe an antibiofilm effect (LOABE) ( 1.5 µM for all the proteins), 3) The specific antibiofilm activity and the percentage of biofilm removal that revealed LysH5 as the best antibiofilm compound. Overall, this technology might be used to quickly assess and compare by standardized parameters the disaggregating activity of phage antibiofilm proteins.